The Dynamic ATP-Driven Mechanism of Bacterial Protein Translocation and the Critical Role of Phospholipids - Collinson, Ian (Frontiers in Microbiology, 2019)
Protein secretion from the cell cytoplasm to the outside is essential for life. Bacteria do so for a range of membrane associated and extracellular activities, including envelope biogenesis, surface adherence, pathogenicity, and degradation of noxious chemicals such as antibiotics. The major route for this process is via the ubiquitous Sec system, residing in the plasma membrane. Translocation across (secretion) or into (insertion) the membrane is driven through the translocon by the action of associated energy-transducing factors or translating ribosomes. This review seeks to summarize the recent advances in the dynamic mechanisms of protein transport and the critical role played by lipids in this process. The article will include an exploration of how lipids are actively involved in protein translocation and the consequences of these interactions for energy transduction from ATP hydrolysis and the trans-membrane proton-motive-force (PMF).